Private capital markets : valuation, capitalization, and transfer of private business interests - 254726 Slee, Robert T. (Hoboken, N.J. : Wiley)
"The private capital markets are the venue where debt and private equity investments are made, and private business interests are exchanged. Valuation is the common language uniting them, enabling participants in private capital markets to communicate and exchange interests. Written for CEOs, CFOs, business appraisers, lawyers, and venture capitalists, this book introduces private capital market theory as an integrated body of knowledge for the valuation, capitalization, and transfer of private companies, especially those with annual revenue between $5 million to $150 million"--